State and federal nuclear support schemes in dynamic electricity market conditions: Insights from NYISO and PJM - Muhammad Maladoh Bah (University of Basel, Center of Business and Economics (WWZ), 2023)
Since 2017, several U.S. states have put in place out-of-market financial support schemes for nuclear power plants operating in deregulated electricity markets. In late 2021, the federal government announced the introduction of two new support schemes to secure the continued operation of nuclear power plants. This policy paper evaluates the profitability of state subsidized nuclear plants in the NYISO and PJM markets over a five-year period between 2017 and 2021. Results indicate that apart from 2019, nuclear power plants were financially robust, relying solely on market revenues without the need for state support schemes. More importantly, the recent upswing in competitive electricity market prices suggests that additional federallevel support schemes are not economically justified in the current market conditions. I provide several suggestions to reconfigure the support schemes to reflect dynamic market conditions and ensure only vulnerable plants are granted out-of-market support
Keywords: H71; Q41; Q48; 330; nuclear support schemes; electricity market; excess profit; NYISO; PJM